Functional Consequences of Metabolic Zonation in Murine Livers: Insights for an Old Story. Issue 2 (7th November 2020) - Berndt, Nikolaus; Kolbe, Erik; Gajowski, Robert; Eckstein, Johannes; Ott, Fritzi; Meierhofer, David; Holzhütter, Hermann‐Georg; Matz‐Soja, Madlen
Abstract : Background and Aims: Zone‐dependent differences in expression of metabolic enzymes along the portocentral axis of the acinus are a long‐known feature of liver metabolism. A prominent example is the preferential localization of the enzyme, glutamine synthetase, in pericentral hepatocytes, where it converts potentially toxic ammonia to the valuable amino acid, glutamine. However, with the exception of a few key regulatory enzymes, a comprehensive and quantitative assessment of zonal differences in the abundance of metabolic enzymes and, much more important, an estimation of the associated functional differences between portal and central hepatocytes is missing thus far. Approach and Results: We addressed this problem by establishing a method for the separation of periportal and pericentral hepatocytes that yields sufficiently pure fractions of both cell populations. Quantitative shotgun proteomics identified hundreds of differentially expressed enzymes in the two cell populations. We used zone‐specific proteomics data for scaling of the maximal activities to generate portal and central instantiations of a comprehensive kinetic model of central hepatic metabolism (Hepatokin1). Conclusions: The model simulations revealed significant portal‐to‐central differences in almost all metabolic pathways involving carbohydrates, fatty acids, amino acids, and detoxification.